Expose/Oppose/Propose: The Canadian Centre for Policy Alternatives and the Challenge of Alternative Knowledge - Carroll, William K.; Huxtable, David (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2014)
This case study explores some of the strategies, challenges, and paradoxes of producing and mobilizing alternative knowledge in the prosecution of a “war of position” against neoliberal hegemony. Since its founding in 1980, the Canadian Centre for Policy Alternatives (CCPA) has become the key labour-supported “think tank” of the left in Canada, contributing to the process of social democratization by acting as a collective organic intellectual for a wide range of oppositional groups and networks that, we suggest, make up a social democratic community of practice. The ccpa has developed a number of strategies aimed at democratizing knowledge production, perhaps unique in the context of Canadian policy groups. Nonetheless, it faces a number of challenges in following through with these strategies and potential paradoxes in simultaneously engaging both the mainstream (general public and policymakers) and the various counterpublics that make up its community of practice.